Effects of non-toxic zinc exposure on human epidermal keratinocytes1. Issue 3 (11th March 2015) - Emri, Eszter; Miko, Edit; Bai, Péter; Boros, Gábor; Nagy, Georgina; Rózsa, Dávid; Juhász, Tamás; Hegedűs, Csaba; Horkay, Irén; Remenyik, Éva; Emri, Gabriella
<x xml:space="preserve">Abstract</x> The exposure of human keratinocytes to non-toxic concentrations of ZnCl2 impacts gene expression, cell proliferation and the response to UVB.